Low-resistivity gas sensors based on the In2O3-Ga2O3 mixed compounds films - Yakovlev, Nikita N.; Almaev, Aleksei V.; Nikolaev, Vladimir I.; Kushnarev, Bogdan O.; Pechnikov, Aleksei I.; Stepanov, Sergey I.; Chikiryaka, Andrei V.; Timashov, R. B.; Scheglov, Mikhail P.; Butenko, Pavel N.; Almaev, Dmitry A.; Chernikov, Evgeniy V. (Materials today communications)
The effect of H2, NH3, CO, CH4, O2 and NO2 on the electroconductive properties of the In2O3-Ga2O3 mixed compounds films obtained by the halide vapor phase epitaxy was studied. In the temperature range of 150–550 °C In2O3-Ga2O3 films are characterized by high responses, high speed of operation when exposed to H2, NH3, CO and O2. A qualitative mechanism of gas sensitivity for the In2O3-Ga2O3 mixed compounds films to gases was proposed. The gas-sensitive characteristics of In2O3, κ(ε)-Ga2O3 and In2O3-Ga2O3 films were compared. The advantage of the In2O3-Ga2O3 mixed compounds films compared with Ga2O3 and In2O3 films is a low base electrical resistivity with a relatively high gas sensitivity.